História natural de Phyllomedusa ayeaye (Anura, Hylidae) na Serra da Canastra, Minas Gerais - Borges, Marília Merli [UNESP] (2015)
A total of 988 species of anuran amphibians are currently known for Brazil. Amphibians are among the most threatened groups nowadays, mostly due to loss and alteration of habitats and diseases. This study describes the natural history of Phyllomedusa ayeaye (Anura: Hylidae) and was conducted in the Brazilian Cerrado, probably the most threatened savanna in the world. The studied stream is located in the Serra Canastra mountain range, Minas Gerais state. Field expeditions were conducted monthly from October 2013 to March 2014 and sporadic observations made in December 2010, January 2011, February 2011, April to June 2011, and December 2014 were considered here. Species' reproductive pattern was intermediate between explosive and prolonged, amplexus was axillary, and the species exhibited the reproductive mode typical for the genus. The number of males calling was significantly correlated with air temperature. From 41 males sampled, we recaptured 14 individuals from one to four times, totalizing 24 recaptures in a time interval of 13 months and a maximum displacement of 40 meters. There was no significant difference in body size between males captured just once and recaptured males. Males called from a variety of calling substrates along a temporary stream, mainly from shrubs of Leandra sp. (Melastomataceae). Females were significantly larger than males. Clutches were found on folded leaves of Leandra sp., containing yellowish eggs with eggless gelatinous capsules. Mean eggs per clutch was 29 ± 2.38 (N = 6) and mean egg diameter was 2.84 ± 0.02 mm (N = 109). The reproductive investment (gonad mass/body mass*100) of females was 4.25 ± 0.35% (N = 3) and that of males was 0.16 ± 0.05% (N = 14). Aggressive behaviors including fights and aggressive calls were registered. Males emitted two types of advertisement calls: a simple call, composed by a sequence of short notes and a composite call, with a sequence of short notes followed by a long ...